Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (Worlds of desire, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis

Sky's the limit: The operations, renovations and implications of a Montréal gay bar - Allan, James (Université McGill, 1997)
Sky, un Hméga-club" en plein essor situé au coeur du village gai de Montréal, représente plusieurs tendances au sein des clubs et des villages gais de l'Amérique du Nord à la fin du XXième siècle. Ce projet aborde les opérations quotidiennes du Sky, en tenant compte de son architecture complexe, de ses pratiques de gestion, et de sa popularité à l'intérieur du village ainsi que des ramifications théoriques de cet établissement pour la communauté gaie et pour la culture des clubs de nuit en général. Au plan théorique, ce complexe récréatif présentement en expansion constitue un phénomène ni complètement opprimant, ni entièrement libérateur. Bien que le Sky offre certains des avantages d'un "méga-club" pour la communauté gaie--plus grande diversité, accessibilité, et communauté--il possède également les désavantages de ces établissements: la concentration du pouvoir économique, une moins grande présence gaie dans les rues, et la promotion de certaines identités et cultures gaies plutôt que d'autres.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; communication; discipline; environnement; espace sécuritaire; identités LGBTQIA2+; montréal; mémoires/thèses; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; travail